PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN IMPLIKASINYA PADA KINERJA KARYAWAN RSIA NORFA HUSADA DI BANGKINANG KOTA - Utami Indah Pratiwi; Zulfadil Zulfadil; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of competence and work motivation on job satisfaction and its implications on the performance of RSIA Norfa Husada employees in Bangkinang City.The population of this study were all employees of RSIA Norfa Husada in Bangkinang City, totaling 55 people. The sample determination in this study was using the census technique. This means that the entire population is sampled. Therefore the number of samples in this study was 55 people. The types of data used are primary and secondary data, while the data collection techniques use questionnaires and literature study. Data analysis using Structural Equation Modeling (SEM).The results of the study show that competence has an effect on employee job satisfaction, work motivation has no effect on employee job satisfaction. Work motivation has an effect on employee performance. Job satisfaction affects employee performance, competence indirectly affects employee performance through job satisfaction. Work motivation has no effect on employee performance through job satisfactionKeywords: competence, work motivation, job satisfaction, employee performance